Nilai-nilai Sosial dalam Tradisi Bakar Kemenyan Pada Masyarakat Desa Sugiharjo Kecamatan Batang Kuis - Kokoh Yeri Kustioro; Mailin Mailin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This research will discuss the tradition of burning Kemenyan in Sugiharjo village based on social values and their relation to religious values. This research aims to determine whether the values contained in this incense burning tradition have a positive value or if this tradition is just to make one comfortable. This study uses a descriptive qualitative method by conducting research directly into the field, observing and interviewing one of the people in the village of Sugiharjo to obtain data sources. The study results show that the tradition of burning Kemenyan in Sugiharjo village is still used to carry out healing rituals and summon the spirits of the dead to be invited to communicate by telling them that they are eternal in the afterlife. This must be done because the nature of Kemenyan, a fragrance, can remind humans that when they die, all the limbs can no longer feel anything except the nose; therefore, the spirits of the dead can return when the Kemenyan is burnt.